NURSING CARE FOR WOMEN WITH GESTATIONAL DIABETES - Mascarenhas da Silva, Hellen; Silva Oliveira, Geane (Health and Society, 2024)
INTRODUCTION: Gestational diabetes is characterized as a multifactorial etiology and difficult to control, which makes a broad approach necessary, in which the success of treatment is directly linked to nursing actions developed for this population, especially in prenatal care. The nurse, as an educator, must guide the pregnant woman regarding the disease, its symptoms and drug therapy, providing guidance on healthy habits, such as nutrition and physical exercise, clarifying doubts during the course of pregnancy and encouraging self-care. OBJECTIVE: To investigate nursing care for women with gestational diabetes in the literature. METHODOLOGY: qualitative research of an exploratory nature, of the integrative review type. The article searches were carried out based on the selection of descriptors registered in DECS (Health Sciences Descriptors): Nursing Care, Gestational Diabetes, High-Risk Pregnancy. Searches for articles were carried out in the virtual health library (VHL), with the help of the Boolean operator “AND”. The online databases used were: LILACS, BDENF - nursing. For the inclusion criteria, the following were used: complete articles available in full, indexed in databases, in Portuguese, with a time frame of the last 10 years (2014 to 2024). Exclusion criteria include: theses, dissertations, reports, abstracts, monographs. RESULTS AND DISCUSSION: According to the eligibility criteria, 18 articles were found in LILACS, BDENF - nursing among the studies searched, 4 of them were selected based on the chosen topic. During the process of reviewing each study, checking the inclusion and exclusion criteria, reading the titles, reading the abstracts, reading the total articles, only 6 studies were selected in this review. CONCLUSION: Therefore, it can be concluded that nurses have an important responsibility during the prenatal care process, with regard to early diagnosis and adequate treatment of gestational diabetes mellitus.